Effects of intravesical prostaglandin E(2) on bladder function are preserved in capsaicin-desensitized rats - Hokanson, James A. (Am J Physiol Renal Physiol, 2021)
Prostaglandin E(2) (PGE(2)) instilled into the bladder generates symptoms of urinary urgency in healthy women and reduces bladder capacity and urethral pressure in both humans and female rats. Systemic capsaicin desensitization, which causes degeneration of C-fibers, prevented PGE(2)-mediated reductions in bladder capacity, suggesting that PGE(2) acts as an irritant (Maggi CA, Giuliani S, Conte B, Furio M, Santicioli P, Meli P, Gragnani L, Meli A. Eur J Pharmacol 145: 105–112, 1988). In the present study, we instilled PGE(2) in female rats after capsaicin desensitization but without the hypogastric nerve transection that was conducted in the Maggi et al. study. One week after capsaicin injection (125 mg/kg sc), rats underwent cystometric and urethral perfusion testing under urethane anesthesia with saline and 100 µM PGE(2). Similar to naïve rats, capsaicin-desensitized rats exhibited a reduction in bladder capacity from 1.23 ± 0.08 mL to 0.70 ± 0.10 mL (P = 0.002, n = 9), a reduction in urethral perfusion pressure from 19.3 ± 2.1 cmH(2)O to 10.9 ± 1.2 cmH(2)O (P = 0.004, n = 9), and a reduction in bladder compliance from 0.13 ± 0.020 mL/cmH(2)O to 0.090 ± 0.014 mL/cmH(2)O (P = 0.011, n = 9). Thus, changes in bladder function following the instillation of PGE(2) were not dependent on capsaicin-sensitive pathways. Further, these results suggest that urethral relaxation/weakness and/or increased detrusor pressure as a result of decreased compliance may contribute to urinary urgency and highlight potential targets for new therapies for overactive bladder.